Branding Through Interior Design: Exploring Theory, and Interpretation - R Mekar Liza Ramadhina; Susy Budi Astuti (RUAS, 2024)
The theory of interior branding is a concept proposed by Kim Kuhteubl (2016) in her book "Branding + Interior Design: Visibility and Business Strategy for Interior Designers". The theory of interior branding explores the role of interior design in reinforcing brand identity and customer loyalty. Discussion regarding this theory can be found in journals/articles that examine the implementation of interior branding in various commercial spaces. Among these discussions are explanations concerning the aspects that contribute to interior branding, such as vision, story, and energy. However, in-depth explanations regarding the meaning of these aspects in forming interior branding are still limited. This limitation poses a risk of generating multiple interpretations of the theory of interior branding. Nevertheless, these aspects can be further elucidated by referencing fundamental theories of interior design. This journal aims to complement the explanations of each aspect that shapes interior branding. A more comprehensive explanation can provide a deeper understanding. The research method employed is a literature review method related to each relevant keyword. The literature review sources are limited to the fields of interior design and architecture to ensure relevance and alignment with the context of the research.